2007
DOI: 10.1002/yea.1462
|View full text |Cite
|
Sign up to set email alerts
|

Microevolution in genomic short sequence repeats of Candida albicans in non‐neutropenic patients

Abstract: The genome of the yeast Candida albicans harbours many genomic short sequence repeats (SSRs). These are stable upon transition of colonization to infection in immune-compromised patients. We show here that in non-neutropenic patients this transition may coincide with variation in several of the SSRs. This may have implications for stage-specific expression of C. albicans pathogenicity factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…2). Previous studies with C. albicans strains also showed that one strain that transitioned from colonization of nonsterile sites to infection of sterile sites could be detected by changes in the short sequence repeat DNA fingerprinting patterns (1,30). Such variation may imply microevolution, which resulted in a transition from colonization to invasion status.…”
Section: Discussionmentioning
confidence: 97%
“…2). Previous studies with C. albicans strains also showed that one strain that transitioned from colonization of nonsterile sites to infection of sterile sites could be detected by changes in the short sequence repeat DNA fingerprinting patterns (1,30). Such variation may imply microevolution, which resulted in a transition from colonization to invasion status.…”
Section: Discussionmentioning
confidence: 97%
“…The main source of invasive C. albicans was confirmed to originate from the endogenous mycobiota (6,130,140,141). Indeed, identity between isolates from blood and colonized anatomical sites was almost always observed, leading to the conclusion that nosocomial transmission between patients is likely a rare event (141,142), even if an outbreak is suspected (143), although some authors have reported nosocomial transmission in hospital environments (144)(145)(146)(147)(148). MLP typing has also been used to track the origin of graft site candidiasis after kidney transplantation (149).…”
Section: Candida Yeasts Candida Albicansmentioning
confidence: 99%
“…However, if an adaptive response to a particular environment is needed, the strain may undergo microevolution (132,141,(150)(151)(152)(153). These genetic variations have been widely observed among closely related strains and are mainly associated with loss of heterozygosity (120,124,125,144). Only a few studies have reported strain replacement with a completely different type of C. albicans (131,132).…”
Section: Candida Yeasts Candida Albicansmentioning
confidence: 99%
“…There is only very limited evidence suggesting possible associations of different TR-ORF alleles with different niches, such as commensalism versus disease [20]. Allele changes that are correlated with the transition from commensal to pathogen would be of great interest, not only because they would improve our understanding of this transition, but also because these could potentially assist in predicting the onset of candidiasis and thus early diagnosis of the disease, an important determinant of survival of life-threatening C .…”
Section: Introductionmentioning
confidence: 99%